Early Self-directed Home Exercise Program After Anterior Cervical Discectomy and Fusion: A Pilot Study. Issue 4 (15th February 2020) - Coronado, Rogelio A.; Devin, Clinton J.; Pennings, Jacquelyn S.; Vanston, Susan W.; Fenster, Dana E.; Hills, Jeffrey M.; Aaronson, Oran S.; Schwarz, Jacob P.; Stephens, Byron F.; Archer, Kristin R.
Abstract : Study Design: Pilot randomized controlled trial. Objective: To examine the acceptability and preliminary safety and outcome effects of an early self-directed home exercise program (HEP) performed within the first 6 weeks after anterior cervical discectomy and fusion (ACDF). Summary of Background Data: Little is known regarding optimal postoperative management after ACDF. Methods: Thirty patients (mean ± standard deviation, age = 50.6 ± 11.0 years, 16 women) undergoing ACDF were randomized to receive an early HEP (n = 15) or usual care (n = 15). The early HEP was a 6-week self-directed program with weekly supportive telephone calls to reduce pain and improve activity. Treatment acceptability was assessed after the intervention period (6 weeks after surgery). Safety (adverse events, radiographic fusion, revision surgery) was determined at routine postoperative visits. Disability (Neck Disability Index), pain intensity (Numeric Rating Scale for neck and arm pain), physical and mental health (SF-12), and opioid use were assessed preoperatively, and at 6 weeks and 6 and 12 months after surgery by an evaluator blinded to group assignment. Results: Participants reported high levels of acceptability and no serious adverse events with the early HEP. No difference in fusion rate was observed between groups ( P  > 0.05) and no participants underwent revision surgery. The early self-directed HEP group reported lower 6-week neck pain than the usual care group ( F  = 3.3, P  = 0.04, r 2  = 0.3, mean difference = −1.7 [−3.4; −0.05]) and lower proportion of individuals (13% vs. 47%) using opioids at 12 months ( P  = 0.05). No other between-group outcome differences were observed ( P  > 0.05). Conclusion: An early self-directed HEP program was acceptable to patients and has the potential to be safely administered to patients immediately after ACDF. Benefits were noted for short-term neck pain and long-term opioid utilization. However, larger trials are needed to confirm safety with standardized and long-term radiograph assessment and treatment efficacy. Level of Evidence: 2 Abstract : Supplemental Digital Content is available in the textA pilot randomized trial examined the acceptability, safety, and preliminary effects of a self-directed home exercise program in patients after anterior cervical discectomy and fusion. The home exercise program was acceptable to patients, appeared safe, and has the potential to be effective in the short-term and mitigate long-term opioid use.